Pertanika Journal of Social Sciences & Humanities
"Legal Eagle" Entrepreneurship Education for Law Students : Special Reference to International Islamic University Malaysia/ Zuhairah Ariff Abd. Ghadas, Herna Muslim & Zarinah Hamid [83-98]